Pengaruh Penambahan Hydroxyapatite Terhadap Struktur Mikro dan Sifat Mekanik Paduan Mg-Al-Zn Melalui Proses Thixoforming - Andy Saputro; Intan Khoerunisa; Kusharjanto Suhirman; Supono Adi Dwiwanto (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2019)
Magnesium alloys are lightweight metallic materials with low mechanical properties. Therefore, in an effort to meet the application requirements for orthopedic implants, the mechanical properties such hardness and tensile strength of Mg-Al-Zn shall be improved. The purpose of this research is to investigate the effect of adding hydroxyapatite (HA) particle to changes in microstructure, hardness and mechanical properties regarding with ultimate strength. HA is a potential compound to be a suitable candidate for applied to orthopedic implants. And thixoforming process is a potential process to be a grain refiner (globular) so as to improvethe mechanical properties magnesium alloy.in this research, the molten Mg-Al-Zn alloy is added HA with a various range of 1.5, 2, 2.5 wt% and then water quenched. Futhermore, Mg-Al-Zn-HA is heated at 530°C (semi-soid temperature) and then thixoforming process is performed. The characterization result as cast showed that increasing of HA content made the smaller dendritic structure. And the result of thixoforming product showed the microstructure is globular grains with maximum hardness value of 86,33 VHN in 2.5% HA and the maximum ultimate tensile strength value of 328.63 MPa in 2% HA with hardness value of 83.42 VHN lower than 2.5% HA alloy. This is due to the presence of porosity in the 2.5% HA alloy with porosity area 4.66 mm2.